2020
DOI: 10.1111/efp.12599
|View full text |Cite
|
Sign up to set email alerts
|

Foliar nematode, Litylenchus crenatae ssp. mccannii, population dynamics in leaves and buds of beech leaf disease‐affected trees in Canada and the US

Abstract: A foliar nematode, Litylenchus crenatae ssp. mccannii, is associated with beech leaf disease (BLD) symptoms. Information about the types of tissues parasitized and how nematode populations fluctuate in these tissues over time is needed to improve surveys as well as understand the nematodes role in BLD. During this study, the nematode was detected throughout the known range of BLD by researchers at both Canadian and US institutions using a modified pan method to extract nematodes. Monthly collections of symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…Beech leaf disease begins within the bud because the leaves are already symptomatic when they break through the bud in early spring [ 4 , 20 ]. Therefore, we quantified the nematode population dynamics within the buds at the beginning of the autumn, when senescent leaves fall, and the buds become the only leaf related structure until the following season.…”
Section: Resultsmentioning
confidence: 99%
“…Beech leaf disease begins within the bud because the leaves are already symptomatic when they break through the bud in early spring [ 4 , 20 ]. Therefore, we quantified the nematode population dynamics within the buds at the beginning of the autumn, when senescent leaves fall, and the buds become the only leaf related structure until the following season.…”
Section: Resultsmentioning
confidence: 99%
“…Given this information, it is possible that lignin levels are higher in the local-naïve beech samples and serving as a barrier to LCM/pathogen infection, which could be responsible for the changes in the spectral profile compared to pre-symptomatic samples. While the exact BLD disease cycle has not been clearly defined, studies show that LCM overwinters in American beech buds as well as attached and detached leaves; live nematodes are found in leaves throughout the growing season with the greatest numbers found in late summer/early fall (Carta et al, 2020;Reed et al, 2020). Since BLD symptoms are present at bud break and do not progress throughout the season (Fearer et al, 2022), this suggests that LCM causes symptoms prior to bud break, which Carta et al (2020) confirmed in their study, and LCM migration into the leaf occurs sometime before September (Reed et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…While the exact BLD disease cycle has not been clearly defined, studies show that LCM overwinters in American beech buds as well as attached and detached leaves; live nematodes are found in leaves throughout the growing season with the greatest numbers found in late summer/early fall (Carta et al, 2020;Reed et al, 2020). Since BLD symptoms are present at bud break and do not progress throughout the season (Fearer et al, 2022), this suggests that LCM causes symptoms prior to bud break, which Carta et al (2020) confirmed in their study, and LCM migration into the leaf occurs sometime before September (Reed et al, 2020). Therefore, it is possible that higher lignin levels in local-naïve leaves are preventing LCM/pathogen infection prior to bud break.…”
Section: Discussionmentioning
confidence: 99%
“…Under highly severe levels of nematode infection, leaves become leathery and crinkled. As the disease progresses in the following years, there is a significant reduction in bud and leaf survival leading to a substantial decrease in the tree canopy, eventually resulting in tree mortality (Burke et al., 2020; Reed et al., 2020). Although this distinct interveinal leaf banding is a hallmark of BLD, it is only observed at advanced nematode infection stages, making early detection challenging.…”
Section: Introductionmentioning
confidence: 99%